Spatial Competition and Ethanol Plant Location Decisions (2012)
Ethanol is one of the fastest growing industries in the United States. This study estimates factors that impact location decisions for new ethanol plants using logistic regression analysis and spatial correlation techniques. The results indicate that location decisions are impacted by county agricultural characteristics, competing ethanol plants, and state-level subsidies. Spatial competition is particularly important. Existence of competing ethanol plants reduces the likelihood of making a positive location decision, and this impact decreases with distance. Finally, state-level subsidies are significant and a very important variable impacting ethanol location decisions. [JEL Classification: C13, C21, C25, C35, Q42]. C 2012 Wiley Periodicals, Inc.